Anxiety cases among Muslim patients: perceptions & managements - Abdul Khaiyom, Jamilah Hanum (2018)
Cognitive Behaviour Therapy (CBT) is one of the treatment of choice in treating patients with Anxiety Disorders (AD) in Malaysia. Current study aims to discuss the perceptions and management of AD among Muslim patients through the adapted Cognitive Behavioural Model. The adaptation of CBT here involves the integration of Malay cultural elements and Islamic rituals. Two cases of Social Anxiety Disorder and Panic Disorder will be discussed. The participants of the study were all Muslims, Malays, either students or staff at one of the public university in Klang Valley, Malaysia. They received the Adapted-CBT from a trained CBT therapist at the psychology clinic in the university. The CBT sessions received range between eight to twelve 1-hour session, face-to-face, and individually. Pre-treatment assessments, middle-treatment assessments, and post-treatment assessments were conducted. Results show reductions in anxiety symptoms, negative thoughts, and comorbid symptoms of depression. Whereas, quality of life was increased at the end of the treatment. Participants also qualitatively reported positive changes in their understanding on Islam. Some of the participants reported the techniques used in the therapy assist them in enhancing their spiritual journey. The results indicate promising improvements among the participants. Hence, the module of Adapted-CBT is hoped to be published. Future studies are encouraged to have more participants and use controlled trial design in assessing the effectiveness of Adapted-CBT. The use of quantitative self-report measures of religiosity and spiritual are also encouraged to be used in the future research.